Examining the Multivariate Relationship Between Emotional Intelligence and Adjustment to College among First-Year College Students Using Canonical Correlation Analysis - Joshua Watson; Allison Joyal; Justen Schroeder (Journal of College Orientation, Transition, and Retention, 2025)
We examined relationships between scores on the Assessing Emotions Scale and Student Adaptation to College Questionnaire among 474 first-year students at a regional university in the Southern United States. Results from the full canonical correlational model indicated that dimensions of emotional intelligence were positively associated with college adjustment experiences, accounting for 22.3% of the variance between the variable sets. Interpretation of the structure coefficients indicated that students’ ability to process and effectively utilize their and others’ emotions supports positive academic adjustment experiences, healthy interpersonal relationships, regulated emotional and physical states, lower psychological discomfort, and a generally positive overall college experience.